9C.07: MULTICENTRE RANDOMISED, DOUBLE BLIND, EVALUATION OF NEBIVOLOL PLUS HCTZ AND IRBESARTAN PLUS HCTZ IN THE TREATMENT OF ISOLATED SYSTOLIC HYPERTENSION IN THE ELDERLY. (June 2015) - Seravalle, G.; Van Bortel, L.; Bombelli, M.; Dell'Oro, R.; Trevano, F. Quarti; Dozio, D.; Makel, W.; Fici, F.; Mancia, G.; Grassi, G.
Abstract : Objective: According to the 2013 ESH/ESC guidelines combination drug treatment is recommended in the treatment of isolated systolic hypertension (ISH) to improve blood pressure (BP) control. The present study was aimed at comparing the antihypertensive effects, tolerability and side effects profile of nebivolol/hydrochlorothiazide vs irbesartan/hydrochlorothiazide combination in elderly patients with ISH. Design and method: 124 ISH patients aged 69.1 ± 3.1 (mean ± SEM) followed by 13 general practictioners in Netherlands and Belgium were enrolled and randomized in a double blind fashion to Nebivolol 5 mg/Hydrochlorothiazide 12.5 mg (NH, n = 62) or Irbesartan 150 mg/Hydrochlorothaizide 12.5 (IH, N = 62) once daily for a 12 week period on sitting office BP, ambulatory BP, 24 hour BP variability, pulse pressure, tolerability and safety profile. Results: 9 pts were withdrawn after randomization. After 12 weeks NH caused a significant greater reduction than IH in sitting SBP (-25.8 ± 1.6 vs -20.6 ± 1.7 mmHg, P < 0.03) and heart rate (HR, -7.0 ± 1.0 vs 2.5 ± 1 b/min, P < 0.01), while the decrease in diastolic and pulse BP showed a non significant tendency to be greater in NH than in IH (-7.4 ± 1.0 and -18.3 ± 1.5 vs -5.0 ± 0.09 and -15.7 ± 1.7 mmHg, P = NS for both). The magnitude of the 24-h, day-time and night-time SBP reduction was almost superimposable in the 2 groups, while HR reduction induced by NH was significantly (P < 0.001) greater during the 24-h, the daytime as well as the nighttime period than that induced by IH. NH caused a significantly greater reduction than IH in 24-h SBP variability, both when expressed as standard deviation (-4.4 ± 2.7 ± vs -2.2 ± 5.1 mmHg, P < 0.02) or as coefficient of variation (-2.0 ± 2.6 vs -0.3 ± 3.4, P < 0.01). This was the case also for pulse pressure and mean BP. Both the 2 drug combinations were well tolerated. Conclusions: These data provide evidence that NH induces an office BP reduction greater than IN but similar effects throughout the 24 hours. NH, however, reduces, at variance from IH, 24-h systolic, mean and pulse BP variability, suggesting a greater protection against a variable known to adversely affect morbidity and mortality in hypertensive patients.